Nitrogen release evaluation from a hydrogel of nanocellulose extracted from banana rachis (Musa paradisiaca) in Andisols and Inceptisols soils of Costa Rica - Garita Mejía, Keilyn Yesenia (2026)
Agriculture is one of the main sectors contributing to the Costa Rican economy, with bananas being one of the agricultural activities contributing the greatest to total national production value. Due to this, the banana rachis was used as a raw material in this article to obtain nanocellulose, and the resultant hydrogel will primarily focus on its behavior in the soil. For this purpose, the banana rachis was established that contains 32.31±0.16% of cellulose and 10.17±0.21% of lignin. A factorial design of 23 was then performed to determine the conditions of the basic hydrolysis to be used, for which a sodium hydroxide concentration of 1.0 % was established, a particle size of 1.5 mm, and a hydrolysis time of 15 minutes. The results obtained by infrared spectroscopy and fluorescence microscopy confirmed the removal of lignin from biomass under these conditions. On the other hand, the nanocellulose obtained was analyzed by transmission electron microscopy which revealed fibers with diameters ranging from approximately 16 nm to 31 nm. This nanocellulose was treated with 30% borax, which allowed shifting the hydrogel's no-return point (the maximum amount of water it can lose without ceasing to be rehydratable) from 38.0% to 27.6%. Finally, irrigation of 32 mm/m2 was applied in a laboratory-scale irrigation system achieving a 20.14% increase in soil nitrogen content for Andisol and 12.96% for Inceptisol.